Effect of a Novel Photoelectrochemical Oxidation Air Purifier on Nasal and Ocular Allergy Symptoms. (June 2018) - Rao, Nikhil G.; Kumar, Ambuj; Wong, Jenny S.; Shridhar, Ravi; Goswami, Dharendra Y.
Background: Photoelectrochemical oxidation (PECO) is a new air purification technology developed to reduce circulating indoor allergens. PECO removes particles as small as 0.1 nm with the destruction of organic matter otherwise not trapped by a traditional filter and removes volatile organic compounds. Objective: We hypothesized that with daily use, the device would reduce user nasal and ocular allergy total symptom scores (TSS) within 4 weeks. Methods: The study was performed among 46 individuals with self-reported allergies using a portable PECO air purifier. Self-reported TSS were calculated at baseline and weekly for 4 weeks following initiation of continuous use of the system. TSS was the sum of total nasal symptom scores (TNSS) and total ocular symptom scores (TOSS) for the week. Results: There was a statistically significant change in overall TSS from baseline to 4 weeks (10.1 at baseline and 4.35 postintervention) resulting in a mean difference of 5.75 (95% confidence interval [CI] 4.32–7.18; P < .0001). There was a statistically significant change in TNSS from baseline to 4 weeks (6.3 at baseline and 3.04 postintervention) resulting in a mean difference of 3.26 (95% CI 2.33–3.19; P < .0001). There was a statistically significant change in TOSS from baseline to 4 weeks (3.82 at baseline and 1.3 postintervention) resulting in a mean difference of 2.52 (95% CI 1.74–3.3; P < .0001). Conclusion: With the use of PECO air purification technology, TSS, TNSS, and TOSS decreased significantly. These improvements were consistent over the 4-week course of device use.